A Study on the Characteristic and Antibacterial Activity of Ti3Ox Thin Films - Endrika Widyastuti (MDPI AG, 2021)
A pure Ti target in Ar/O2 gas mixture was used to synthesize Ti3Ox thin film on a glass substrate by Reactive High-Power Impulse Magnetron Sputtering (HiPIMS) under different sputtering power (2 and 2.5 kW). The influence of HiPIMS parameters on thin films’ structural, morphological, chemical composition, optical and photocatalytic, and antibacterial properties was investigated. In this study, Ti3Ox thin films can be synthesized using the HiPIMS method without the post-annealing process. Two co-existence phases (hexagonal Ti3O and base-centered monoclinic Ti3O5 phases) existed on the Ti3Ox films. It is found that the peak intensity of (006) Ti3O hexagonal slightly increased as the sputtering power increased from 2 to 2.5 kW. The Ti3Ox thin-film bandgap values were 3.36 and 3.50 eV for 2 and 2.5 kW, respectively. The Ti3Ox films deposited at 2.5 kW showed good photocatalytic activity under UV light irradiation, with a higher methylene blue dye degradation rate than TiO2 thin films. The antibacterial study on Ti3Ox thin films exhibited a high inhibition percentage against E. coli and S. aureus. This study demonstrates that Ti3Ox thin films can promote high photocatalytic and antibacterial activity.